Teologi Ibrahim dalam Perspektif Agama Yahudi, Kristen, dan Islam - Muhammad Afdillah (Universitas Darussalam Gontor, 2016)
This paper is intended to examine the theology of Abraham who is the father of Judaism, Christianity, and Islam. The three religions have debated on several issues and fought in several battles. The one way is to break the wall that stood around them to know the origin of the three religions. Here, Ibrahim is a single actor as a way to answer the similarities and differences of the three religions. The story of Ibrahim still inspires the believer of all three faiths to become good Jews, Christians, and Muslims. Because the Abrahamic ethic is to maintain the pure monotheism, that there is no god except Allah, without any interruption and intervention of paganism and polytheism. Generally, this research is based on the history of mankind, and focuses on the study of the Bible and the Holy Qur’an. Through this research, the writer found few differences and similarities in the Bible and the Qur’an about the life of Abraham. Firstly, that Abraham will be the patriarch of the nations and the major religions. Secondly, Abraham is spiritual journey which an inspiration for Jews, Christians, and Muslims in performing their religious rituals. Then, the writer also found that the theological concept built by Abraham is monotheistic (tawhi>d) and totally (ka>ffah) self-surrendering (aslama) totally to the Almighty God; rejecting all forms paganism and polytheism.